Acclimation of nitrogen uptake capacity of rice to elevated atmospheric CO(2) concentration - Shimono, Hiroyuki (Oxford University Press, 2009)
BACKGROUND AND AIMS: Nitrogen (N) is a major factor affecting yield gain of crops under elevated atmospheric carbon dioxide concentrations [CO(2)]. It is well established that elevated [CO(2)] increases root mass, but there are inconsistent reports on the effects on N uptake capacity per root mass. In the present study, it was hypothesized that the responses of N uptake capacity would change with the duration of exposure to elevated [CO(2)]. METHODS: The hypothesis was tested by measuring N uptake capacity in rice plants exposed to long-term and short-term [CO(2)] treatments at different growth stages in plants grown under non-limiting N conditions in hydroponic culture. Seasonal changes in photosynthesis rate and transpiration rate were also measured. KEY RESULTS: In the long-term [CO(2)] study, leaf photosynthetic responses to intercellular CO(2) concentration (Ci) were not affected by elevated [CO(2)] before the heading stage, but the initial slope in this response was decreased by elevated [CO(2)] at the grain-filling stage. Nitrate and ammonium uptake capacities per root dry weight were not affected by elevated [CO(2)] at panicle initiation, but thereafter they were reduced by elevated [CO(2)] by 31–41 % at the full heading and mid-ripening growth stages. In the short-term study (24 h exposures), elevated [CO(2)] enhanced nitrate and ammonium uptake capacities at the early vegetative growth stage, but elevated [CO(2)] decreased the uptake capacities at the mid-reproductive stage. CONCLUSIONS: This study showed that N uptake capacity was downregulated under long-term exposure to elevated [CO(2)] and its response to elevated [CO(2)] varied greatly with growth stage.